Analysis of Community Participation in Maritime Tourism Productivity Development Based on Social Capital (Study in Padang Betuah Village, Pondok Kelapa District, Central Bengkulu Regency) - Zaidina Angkasa; Alexsander Alexsander; Harmiati Harmiati; Heru Purnawan; Parwito Parwito (Journal of Social Science and Humanities, 2022)
This study aims to examine or determine the participation of the Padang Betuah village community in creating tourism in the Padang Betuah village, Pondok Kelapa District, Central Bengkulu Regency. This study uses a qualitative descriptive approach. Data collection techniques by conducting interviews, observation and documentation. Informants in the study were the Village Head, Head of BPD, Secretary of BPD, Head of Bumdes, Head of People, Head of Youth Organization and Tourism Manager in Padang Betuah Village, Pondok Kelapa District, Central Bengkulu Regency. From the results of the study, it can be concluded that the participation of ideas when developing the Gedang Lake tourism can be concluded that participation has been carried out to the maximum. Judging from the results of interviews, the participation given in terms of this planning has been maximized, as evidenced by the many plans that have been planned by the Village Head, BPD and the Secretary of the BPD, BumDes, Tourism Managers, Youth Organizations, and Heads of People who have given participatory thoughts about what is being done. will be built and developed in Lake Gedang. Participation in this implementation has not run optimally due to the many obstacles when carrying out a development that has been planned by the community, such as constrained by non-existent funds, obstacles on land which in fact is privately owned and has been used as plantation land. Participation in the utilization of these results does not yet exist because the results obtained from tourist attractions are not included in the income of BumDes but to private or private so that the community certainly cannot reuse the results that have been obtained from the Lake Gedang tourist spot. Participation in this evaluation has not been maximized because many plans have not been fully implemented, due to many obstacles during implementation.